Disitamab vedotin: a novel antibody-drug conjugates for cancer therapy - Fan Shi; Yanli Liu; Xuexiao Zhou; Pei Shen; Ran Xue; Min Zhang (Drug Delivery, 2022)
Human epidermal growth factor receptor 2 (HER2) regulates cell mitosis, proliferation, and apoptosis. Trastuzumab is a HER2-targeted monoclonal antibody (mAB), which can prolong the overall survival rate of patients with HER2 overexpression in later periods of gastric cancer and breast cancer. Although anti-HER2 monoclonal antibody has a curative effect, adjuvant chemotherapy is still necessary to upgrade the curative effect maximumly. Antibody-drug conjugate (ADC) is a kind of therapeutic drug that contains antigen-specific antibody and cytotoxic payload, which can improve the survival time of tumor patients. To date, there are several HER2-ADC products on the market, for which two anti-HER2 ADC (trastuzumab emtansine and trastuzumab deruxtecan) have been authorized by the FDA for distinct types of HER2-positive carcinoma in the breast. Disitamab vedotin (RC48) is a newly developed ADC drug targeting HER2 that is comprised of hertuzumab coupling monomethyl auristatin E (MMAE) via a cleavable linker. This paper aims to offer a general insight and summary of the mechanism of action and the currently completed and ongoing clinical studies of RC-48 in HER-2 positive solid tumors.